Quality preservation of date palm (Phoenix dactylifera L.) fruits at the Khalal stage: a review on current challenges, preservation methods, and future trends - Alqahtani, Nashi K.; Ali, Salim A.; Alnemr, Tareq M. (Frontiers in Sustainable Food Systems, 2025)
Date palm fruits have great commercial value and spiritual and cultural significance in multiple countries due to their high nutritional value and various health benefits. Some popular date varieties such as Barhi, Hayani, Samany, and Zaghlol are harvested at the Khalal stage due to their unique organoleptic properties, including crunchy texture, delicious taste, and attractive color; therefore, they have a great consumer demand and significant market relevance. However, dates at the Khalal stage are facing three issues: (1) they are perishable due to the higher moisture and sugar content, (2) they are rapidly converted from the Khalal to Rutab stage (ripening), and (3) the short picking season, where huge quantities of the fruits reach the horticultural ripening during a short time. Therefore, delaying ripening, maintaining freshness, preventing spoilage, and extending the shelf-life represent the major challenges at the Khalal stage. Accordingly, this review discussed the main factors responsible for quality loss and shelf-life shortening of Khalal dates. Preservation methods, research needs, and future trends were also discussed.